Organ Length Control by an ADAMTS Extracellular Protease in Caenorhabditis elegans. Issue 5 (1st May 2016) - Shibata, Yukimasa; Kawakado, Yuri; Hori, Noriyoshi; Tanaka, Kota; Inoue, Ryo; Takano, Tomomi; Kubota, Yukihiko; Nishiwaki, Kiyoji
Abstract: MIG-17, a secreted protease of the ADAMTS family, acts in the directed migration of gonadal distal tip cells (DTCs) through regulation of the gonadal basement membrane in Caenorhabditis elegans . Here, we show that MIG-17 is also required for the control of pharynx elongation during animal growth. We found that the pharynx was elongated in mig-17 mutants compared with wild type. MIG-17 localized to the pharyngeal basement membrane as well as to the gonadal basement membrane. The number of nuclei in the pharynx, and the pumping rate of the pharynx, were not affected in mig-17 mutants, suggesting that cells constituting the pharynx are elongated, although the pharynx functions normally in these mutants. In contrast to the control of DTC migration, MIG-18, a secreted cofactor of MIG-17, was not essential for pharynx length regulation. In addition, the downstream pathways of MIG-17 involving LET-2 /type IV collagen, FBL-1 /fibulin-1, and NID-1 /nidogen, partly diverged from those in gonad development. These results indicate that basement membrane remodeling is important for organ length regulation, and suggest that MIG-17 /ADAMTS functions in similar but distinct molecular machineries in pharyngeal and gonadal basement membranes.